Photocatalytic Producation of Hydrogen from Aqueous Methanol Solution over Pt/TiO2-Cu2O Under Visible Irradiation - Han, Chenghui; Li, Zhiyu; Shen, Jianyi (Asian Journal of Chemistry, 2015)
Pt/TiO2-Cu2O photocatalysts were prepared in the experiments. For these complex oxides, morphology, structure, composition and optical properties were investigated by HRTEM, XRD, ICP and UV-visible techniques, respectively. In addition, in the absence of oxygen, the photocatalytic generation of H2 from methanol over Pt/TiO2-Cu2O under visible light was studied and the effects of Pt content and composition of catalyst on photocatalytic activity were elucidated. The result showed Pt was deposited on the surface of TiO2-Cu2O in a clustered manner with particle size of 5-20 nm. When Pt content reached 1 wt. %, such catalyst exhibited highest photocatalytic activity. After the catalyst of 1 % Pt/5 % TiO2-Cu2O used for 7 times, the photocatalytic activity in the generation from aqueous methanol of hydrogen remained relatively stable. The catalyst of Pt/TiO2-Cu2O photocatalytic generation of hydrogen from methanol solution achieved through the photo-generated electron of e- reduction of H2O to produce H2. As a result, 327 μmol H2 was obtained after 3 h.